The GCM‐FE Method for the Advanced Analysis of Steel Frameworks and Connections. Issue 6 (30th December 2022) - Yan, Shen; Wan, Wodong; Rasmussen, Kim J.R.
Abstract: The Generalised Component Method (GCM) has recently been formulated for analysing the full‐range nonlinear response of connections, incorporating the elastic and inelastic stiffnesses, the post‐ultimate softening as well as the ductility of each component. In this paper, the GCM is implemented in an FE analysis framework of steel structural frames. The paper explains the key elements of the FE modelling, such as the integration of the connection model with adjoining members, the accurate representation of components, and the automatic modelling technique using Python scripts. The framework, termed the GCM‐FE joint modelling method, is then validated against experimental results for bolted top‐and‐seat angle connections, and used to analyse a two‐storey four‐bay irregular steel frame. The GCM‐FE analysis is shown to provide substantially greater insight into the performance of connections than the simplified joint models used in traditional analysis. It not only provides the ultimate resistance and failure mode of the frame, considering both members and connections, but also accurately predicts the load‐redistribution process inside the connections and the resultant effect on the structural framework. The GCM‐FE analysis presents a major step towards the complete direct design of steel frameworks by advanced analysis, and lays the foundation for the next generation of structural design standards in which the strength and structural safety checks of both members and connections are performed in a single step at system level.